2016
DOI: 10.7567/apex.9.112701
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superhydrophobic silicone rubber by ArF-excimer-laser-induced microstructuring for repelling water in water

Abstract: Microswellings of 1 µm height, 1.5 µm diameter, and regular intervals of 2.5 µm on a silicone rubber surface were fabricated using a 193 nm ArF excimer laser. The laser was focused on silicone by each microsphere made of silica glass of 2.5 µm diameter; these microspheres covered the entire surface of the silicone. The surface underneath each microsphere selectively swelled owing to the photodissociation of the Si–O bonds of silicone. The contact angle of water was measured to be approximately 155°, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 19 publications
2
52
0
Order By: Relevance
“…Moreover, this swelling phenomenon was shown to be induced even with an ArF excimer laser (wavelength: 193 nm), as distinct from modification into SiO 2 . Thus, we confirmed that silicone rubber surface can be provided with superhydrophobicity through local irradiation using an ArF excimer laser to perform depolymerization due to photodissociation of main chain structure, and to create a periodic microswelling structure, without modification into SiO 2 …”
Section: Introductionsupporting
confidence: 72%
See 3 more Smart Citations
“…Moreover, this swelling phenomenon was shown to be induced even with an ArF excimer laser (wavelength: 193 nm), as distinct from modification into SiO 2 . Thus, we confirmed that silicone rubber surface can be provided with superhydrophobicity through local irradiation using an ArF excimer laser to perform depolymerization due to photodissociation of main chain structure, and to create a periodic microswelling structure, without modification into SiO 2 …”
Section: Introductionsupporting
confidence: 72%
“…19 Thus, we confirmed that silicone rubber surface can be provided with superhydrophobicity through local irradiation using an ArF excimer laser to perform depolymerization due to photodissociation of main chain structure, and to create a periodic microswelling structure, without modification into SiO 2 . [20][21][22] In this paper, we continue the previous research toward further improvement of superhydrophobicity of silicone rubber surface with a periodic microswelling structure; particularly, we show that when Al thin film is deposited, the surface does not become flat, but a fine texture appears. As a result, contact angle of the sample surface with water increases due to Al film deposition.…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…Recently, when the ArF excimer laser irradiated a silicone rubber, instead of F 2 laser, the photochemical swelling phenomenon which is due to the photodissociation of Si-O bonds of silicone rubber was found on the surface [19,20]. Microspheres made of SiO 2 in micron size were used for fabricating the periodic microswelling structure of silicone rubber, resulting in high superhydrophobic properties [21,22].…”
Section: Introductionmentioning
confidence: 99%